HUBUNGAN SELF-EFFICACY DENGAN PERILAKU NYERI PADA PASIEN KANKER PAYUDARA - Hasnizar Hasnizar (Jurnal Keperawatan Priority, 2022)
Breast cancer is a disease that mostly affects women. One of the symptoms of physical disorders that are often experienced is pain complaints. Pain behavior is an aspect that concerns the experience of pain. Therefore, it is necessary to strengthen psychological factors by increasing cognitive abilities. One of the cognitive abilities is self-efficacy to help recognize emotional responses to pain and train them to control disturbances that originate from the pain they experience. The study aims to determine the relationship between self-efficacy and pain behavior in breast cancer patients at the Royal Prima Hospital Medan. The research method was an analytic survey with a cross sectional approach. The population in this study were 11 people and the research sample was 11 people. The data were processed and analyzed using the Chi-square test with a degree of significance (α) = 0.05. The results is a relationship between self-efficacy and pain behavior in breast cancer patients where the calculation results are X2count 11,000> X2table 9.49 and p value = 0.027. The conclusion of this study is that there is a relationship between self-efficacy and pain behavior in breast cancer patients. For medical personnel to provide motivation so that cognitive abilities, especially self-efficacy in breast cancer patients, increase.